2021
DOI: 10.37394/232015.2021.17.30
|View full text |Cite
|
Sign up to set email alerts
|

Use of Financial Ratios in selecting entities for Tax Audit purposes – empirical study in Albania

Abstract: Information from financial statements and reported financial ratios have long been used to detect common phenomenon such as fraudulent financial statements, earnings management, and the relation between financial ratios and the level of tax risk of an entity. The focus of this study is to research the use of financial ratios that entities declare, in the detection of the magnitude of tax avoidance. In this paper we apply a binary logistic regression to detect which financial statement ratios differentiate betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…Las diversas investigaciones sobre análisis de ratios y estados financieros se constituyen en una herramienta guía para saber cómo interpretar los estados financieros de compañías de todo el mundo (Shkurti, Myftaraj y Gjika, 2021); útiles tanto al estudiante como al empresario. Conjuga herramientas tales como: El análisis horizontal y vertical más la interpretación de indicadores (Tran, Nguyen y To, 2020).…”
Section: El Informe De Análisis Financiero Y De Rentabilidadunclassified
“…Las diversas investigaciones sobre análisis de ratios y estados financieros se constituyen en una herramienta guía para saber cómo interpretar los estados financieros de compañías de todo el mundo (Shkurti, Myftaraj y Gjika, 2021); útiles tanto al estudiante como al empresario. Conjuga herramientas tales como: El análisis horizontal y vertical más la interpretación de indicadores (Tran, Nguyen y To, 2020).…”
Section: El Informe De Análisis Financiero Y De Rentabilidadunclassified
“…By optimizing the capital structure, the company's value, flexibility, and competitiveness may all be increased. Economists have recognised tax shields as a component of capital structure for more than 50 years (Gregova et al, 2021), and companies used to compromise the financial statement data and reported financial ratios for tax avoidance (Shkurti et al, 2021). Managers or owners are generally responsible for handling them, and their motivations may vary.…”
Section: Introductionmentioning
confidence: 99%